Precompetition Cardiac Assessment of Football Players Participating in the 2006 FIFA World Cup Germany - Thünenkötter, T.; Schmied, C.; Grimm, K.; Dvorak, J.; Kindermann, W. (Clinical Journal of Sport Medicine, 2009)
Objectives: To develop a precompetition medical assessment (PCMA) of elite football players aimed at identifying risk factors for sudden cardiac death.